PTU-184 Is there a relationship between gluten ingestion and postural tachycardia syndrome?. (22nd June 2015) - Penny, HA; Ferrar, M; Atkinson, J; Hoggard, N; Hadjivassiliou, M; West, JN; Sanders, DS
Abstract : Introduction: Postural tachycardia syndrome (PoTS) is a group of disorders of autonomic dysfunction, characterised by orthostatic intolerance. Patients often also complain of gastrointestinal (GI) disturbance including abdominal pain, bloating and altered bowel habit. These symptoms are also common in coeliac disease (CD) and non-coeliac gluten sensitivity, along with non-GI symptoms such as fatigue. Despite this overlap, the relationship between CD, gluten sensitivity (GS) and PoTS has not been previously evaluated. We aimed to determine the prevalence of CD in a cohort of patients with PoTS and to assess the frequency and patient characteristics of self-reported GS in this group. Method: The case notes of all patients diagnosed with PoTS who presented to the syncope clinic over the period of one year were reviewed. Concurrently, 100 PoTS patients were recruited to complete a validated questionnaire which screened for GS and related symptoms. Patients on a gluten-free diet (GFD) were asked to rank the severity of abdominal pain and orthostatic intolerance before and after starting GFD using a Likert scale (1 unaffected; 10 severely affected). Results: 4/109 (3.7%) PoTS patients had biopsy-proven CD (3 female; median age 24 years). This was higher than the local population prevalence of CD (0.8%; OR 4.5, 95% CI 1.2–17.2, p = 0.02). 1 The self-reported prevalence of GS was 42% (94% female; median age 27 years), of whom 64% (27/42) were on a GFD. 29% (11/42) of GS patients had been investigated in secondary care; 4/11 had biopsy-proven CD, 1/11 had positive IgA tTG and gliadin serology with negative biopsy, 6/11 had negative serology and biopsy. 38% (16/42) of GS patients had never seen a doctor regarding their GI symptoms. Patients with GS reported an increased incidence of abdominal pain (76% vs. 48%; p = 0.007), but similar prevalence of pain fulfilling the Rome III criteria for IBS (43% vs. 33%; p = 0.15), in comparison with those without GS. Patients felt their abdominal pain improved after starting a GFD (median score 8 to 4, respectively; p = 0.0001), but no change in symptoms of orthostatic intolerance (p = 0.084). Conclusion: The data suggests that CD is more common in PoTS than the general population. Recent evidence suggests an autoimmune basis for PoTS and this could be a common pathological mechanism. There is also a high incidence of self-reported GS in this group, with a large proportion not having been investigated in primary or secondary care. Further research is required to ascertain the nature of the relationship between the gluten-related disorders and PoTS. Disclosure of interest: None Declared. Reference: Sanders DS, Patel D, Stephenson TJ, et al . Eur J Gastroenterol Hepatol. 2003;15(4):407–413